Webrings: social circles of bloggers on the web - Sá, Jéssica Patrícia Silva de (2020)
This article aims to discuss the concept of webrings and how the processes of formation of these social circles of bloggers on the web. Bloggers establish virtual relationships with one another by reading their blogs on a one-to-one basis and getting in touch through comments, creating virtual relationships and communities. Based on virtual ethnography, this research consisted of immersion in the blogosphere, and subsequent interviews with eight bloggers. The results and the discussion about the webrings belonging to the blogosphere highlighted the interaction between bloggers, the sharing of information and the communicative exchanges that take place within these social circles. It has been found that, in most cases, webrings are formed both in virtual and in person, through events and face-to-face meetings. Thus, the investigation of how the webrings are formed suggests the extension of the concept, incorporating the current dynamics of the virtual relations that occur with the influence of the social networks.